The Relationship Between Self-Confidence and Speaking Ability among the Private Islamic Junior High School Students - Erniyanti Nur Fatahhela Dewi; Mentari Pratami (Journal of English Language Learning, 2024)
Self-confidence has an essensial part to start any actions, especially for speaking foreign language. This research was aimed to see the relationship among students’ self-confidence and speaking ability. The research’s instruments were questionnaire of self-confidence and speaking ability test. This research used regression and correlation analysis to find out the relationship between the variables. The results indicated that there was a significant relationship between students' self-confidence and speaking ability. It can be concluded that there was a strong relationship between the variables. Therefore, this research suggested the importance of increasing students’ self-confidence. All of these implications contribute to increasing students’ speaking ability in oral descriptive essays.